Regional Disparities and Determinants of Poverty in Papua: Klassen Typology Analysis and Panel Data Regression - Sanefaro Infun J; Evi Gravitiani; Sarjiyanto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study was conducted to analyze economic development imbalances in various districts/cities in Papua and the determinants of poverty levels by applying Klassen's typology and panel data regression. The results of mapping using Klassen's typology indicate that most districts/cities in Papua are located in Quadrant IV (relatively underdeveloped areas) with lower average per capita income and economic growth compared to the provincial average. This situation is generally experienced by isolated mountainous and coastal areas that face problems in terms of infrastructure, accessibility, and dependence on traditional primary sectors. Meanwhile, panel data regression analysis using the Fixed Effect Model reveals that per capita income and income inequality (Gini Ratio) contribute positively and significantly to an increase in poverty rates. Conversely, the Human Development Index (HDI) has a negative and significant influence, indicating that improvements in the quality of education, health, and living standards can help reduce poverty rates. Meanwhile, economic growth and the open unemployment rate (Unemp) do not show a significant impact in explaining poverty variations. These findings indicate that Papua's development strategy needs to focus on strengthening the HDI and more equitable distribution of development outcomes so that economic growth can have a more inclusive impact